Tumbuhan Pewarna yang Digunakan Masyarakat Dayak Iban Dusun Sungai Utik Kalimantan Barat - Wahdina; Dede Setiadi; Y. Purwanto; Ibnul Qayim (The Ethnobiological Society of Indonesia, 2021)
Sungai Utik Village is one of the ecotourism villages in Kapuas Hulu District, West Kalimantan, Indonesia. The Dayak Iban live in the village in a traditional house called rumah betang. They depend on farming and foraging, weaving and plaiting various types of equipment for their subsistence and economic purpose, and they also manage ecotourism in their village. The people of Dayak Iban were managing the Menua Customary Forest since their old generations. In 2020, the right of the Menua Customary Forest was officially confirmed by the Indonesian Government. In this study, we reviewed the dye plant species used by the people of Sungai Utik Village for various purposes. The data were obtained using semi-structured interviews with local communities. There were 14 species of dye plants used by the Dayak Iban people in Sungai Utik Village, mainly used for dyeing yarn for weaving, and rattan for craft-plaiting. Some of the dye plants were used both for weaving and for plaiting, others were used only for one purpose.